Em busca do tempo perdido : tradição e modernidade em Cuiabá, Mato Grosso na década de 1940 - Sepúlveda, Iza Debohra Godoi (2017)
This paper intents to analyses the Zulmira Canavarros’s theatric works in search of the representations of the modernization process in Cuiabá, Mato Grosso. To this research, we also collected documents like the newspaper O Estado de Mato Grosso (august/1939- november/1944), the A Violeta magazine (January/1940- december/944), the Pindorama magazine (1939). The amount of documents also includes the memories: Cuiabá ao longo de cem anos (Maria Arruda Müller and Dunga Rodrigues) and Memórias de um Cuiabano Honorário (Cassio Veiga de Sá, an engineer who was responsible for the very principal official works in the state of Mato Grosso). Therefore, this work tries to show how the elites of Mato Grosso built a modernization discourse. Show up these discourses from an artistic work results, also, in a historiographic discussion, in the time that we could mark some contradiction and ambiguities about hegemonic interpretations from the moment known as Estado Novo, in special between the years of 1940 and 1945.